Infection and colonization of tissues of the aphid Myzus persicae and cassava mealybug Phenacoccus manihoti by the fungus Beauveria bassiana - Amnuaykanjanasin, Alongkorn; Jirakkakul, Jiraporn; Panyasiri, Cheerapha; Panyarakkit, Pairat; Nounurai, Prachumporn; Chantasingh, Duriya; Eurwilaichitr, Lily; Cheevadhanarak, Supapon; Tanticharoen, Morakot (BioControl (Dordrecht, Netherlands), 2013)
Histopathogenesis of living insects of Myzus persicae Sulzer (Hemiptera: Aphididae) and Phenacoccus manihoti Matile‐Ferrero (Hemiptera: Pseudococcidae) by Beauveria bassiana (Balsamo) Vuillemin (Ascomycota: Hypocreales) was monitored from penetration through insect death. Important events in aphids included fungal penetration of the integument of the less-resistant leg intersegmental membrane and invasion of natural openings, formation of hyphal bodies in live aphids by three days post-inoculation (PI), and extensive hyphal colonization of the two leg segments closest to the insect body at death of the aphids. Confocal microscopy of green fluorescent protein-labeled B. bassiana in live mealybugs indicated the fungus penetrated the host through the legs and mouthparts. The fungus was scarce in live mealybugs at 1–5 days PI, formed hyphal bodies by six days PI, and growth was limited to parts of dead hosts at 6–7 days PI. In dead mealybugs, hyphal bodies were near solid tissue. Blastospores were in the hemolymph.